FEASIBILITY OF ESTIMATING FIBROMUSCULAR DYSPLASIA PREVALENCE USING HEALTH ADMINISTRATIVE DATABASE: A NATIONWIDE STUDY. (June 2018) - Looten, V.; Chatellier, G.; Jantzen, R.; Fiquet, B.; Chedid, A.; Amar, L.; Bobrie, G.; Katsahian, S.; Burgun, A.; Jannot, A.S.; Jeunemaitre, X.; Plouin, P.-F.; et al.
Abstract : Objective: Fibro-muscular dysplasia (FMD) is a non-atherosclerotic and non-inflammatory vascular disease, occurring mainly in women aged 30–50 years. Its prevalence is not well-known and possibly underestimated due to asymptomatic forms. Our aim was to determine whether the French national summary discharge database could be used to estimate the prevalence of FMD. Design and method: Patients were selected by the first occurrence of the I773 ICD-10 code. This code was chosen after an exploratory analysis and advice from national hypertension specialists. In the French national summary discharge database system, all hospitalizations can be linked for a given patient. The zip code of residence was used for geographical analysis. We computed rates of prevalence by an indirect age- and sex-standardization. Results: Between 2008 and 2016, we identified 2798 patients (65.2% female; median age 55y IQR = [43.0–67.0]), for a total of 10835 stays (74.9% of patients had less than 2 stays) of which only 4061 contained the I773 code. No major change in annual incident cases was observed between 2008 to 2016: 317 (11.3%), 342 (12.2%), 292 (10.4%), 309 (11.0%), 299 (10.7%), 319 (11.4%), 294 (10.5%), 279 (9.97%) and 347 (12.4%), respectively. The most common associated codes were I10 (hypertension, 49.0%), I15.0 (vascular/renal hypertension, 19.7%) and E780 (essential hypercholesterolemia, 11.9%). Among all French hospitals, the largest number of patients was identified in the Paris University Hospitals, especially ESH excellence centers (15.7%) and 8 additional University Hospitals belong to the 'top 10' recruiting centres. Using indirect standardization, we observed a geographical disparity with a low prevalence in the East/South-West part of France, which may indicate under-diagnosis of the disease and a very high unexplained prevalence in a single hospital. Figure. No caption available. Conclusions: Both the stable estimate of yearly incident cases and demographic characteristics of the population study are consistent with the literature. Nevertheless, the observed geographical disparity suggests a diagnostic bias. We conclude that the use of the French national summary discharge database alone cannot provide a reliable estimation of the FMD prevalence. Both harmonization of diagnosis procedures and hospitalization coding could help identifying FMD patients in addition to existent multicentric registries.